Critical role of FGF21 in diabetic kidney disease: from energy metabolism to innate immunity - Liang, Yingnan; Chen, Qi; Chang, Yue; Han, Junsong; Yan, Jiaxin; Chen, Zhenjie; Zhou, Jingwei (Frontiers in Immunology, 2024)
Diabetic kidney disease (DKD) stands as the predominant cause of chronic kidney disease (CKD) on a global scale, with its incidence witnessing a consistent annual rise, thereby imposing a substantial burden on public health. The pathogenesis of DKD is primarily rooted in metabolic disorders and inflammation. Recent years have seen a surge in studies highlighting the regulatory impact of energy metabolism on innate immunity, forging a significant area of research interest. Within this context, fibroblast growth factor 21 (FGF21), recognized as an energy metabolism regulator, assumes a pivotal role. Beyond its role in maintaining glucose and lipid metabolism homeostasis, FGF21 exerts regulatory influence on innate immunity, concurrently inhibiting inflammation and fibrosis. Serving as a nexus between energy metabolism and innate immunity, FGF21 has evolved into a therapeutic target for diabetes, nonalcoholic steatohepatitis, and cardiovascular diseases. While the relationship between FGF21 and DKD has garnered increased attention in recent studies, a comprehensive exploration of this association has yet to be systematically addressed. This paper seeks to fill this gap by summarizing the mechanisms through which FGF21 operates in DKD, encompassing facets of energy metabolism and innate immunity. Additionally, we aim to assess the diagnostic and prognostic value of FGF21 in DKD and explore its potential role as a treatment modality for the condition.